Analisis Faktor-Faktor yang Mempengaruhi Ketepatan Waktu Penyampaian Laporan Keuangan (pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Muhsin, Nurul Izza Nujumuddin; Indriani, Eni (Fakultas Ekonomi dan Bisnis Unram, 2024)
This research is intended to examine the influence of good corporate governance, liquidity, company age, and leverage on reporting time measurements in manufacturing companies listed on the IDX for the 2020-2022 period. The type of research used is associative quantitative research. The sample was obtained using a purposive sampling method and 20 companies were selected whose data would be analyzed using the logistic regression method. Based on the results of data processing, it can be concluded that good corporate governance variables, liquidity variables and company age have a significant effect on reporting time, while the leverage variable has no effect on reporting time.